2014
DOI: 10.2147/jmdh.s65153
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes about lung cancer: stigma, support, and predictors of support

Abstract: IntroductionLung cancer is the leading cause of cancer death, yet public engagement with efforts against lung cancer is low. Public engagement with a cancer is critical to efforts to combat it, yet the reasons for low support for efforts against lung cancer have not been systematically characterized.MethodsWe conducted a telephone survey of 1,071 people to determine levels of engagement and attitudes that might potentially drive engagement. These were then analyzed by univariate and multivariate analysis.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…The influence of cancer type was not significant, however, a trend was noted with participants in the 'lung cancer' category reporting lower strengths, which is consistent with previous research (Mosher, Given, & Ostroff, 2015). Negative attitudes related to lung cancer including stigma and disease progression, have been linked to patients' negative perception of their personal strengths and ability to recover (Milbury, et al, 2013;Weiss, Stephenson, Edwards, Rigney, & Copeland, 2014). Nurses' awareness of attitudes towards patients and families across all cancer types is important in order to improve their perception of coping with cancer (Mosher, et al, 2015;Udo, Melin-Johansson, Henoch, Axelsson, & Danielson, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…The influence of cancer type was not significant, however, a trend was noted with participants in the 'lung cancer' category reporting lower strengths, which is consistent with previous research (Mosher, Given, & Ostroff, 2015). Negative attitudes related to lung cancer including stigma and disease progression, have been linked to patients' negative perception of their personal strengths and ability to recover (Milbury, et al, 2013;Weiss, Stephenson, Edwards, Rigney, & Copeland, 2014). Nurses' awareness of attitudes towards patients and families across all cancer types is important in order to improve their perception of coping with cancer (Mosher, et al, 2015;Udo, Melin-Johansson, Henoch, Axelsson, & Danielson, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…The process is usually activated in certain situations of serving or helping another person (Weiner 1980a), hence it is introduced in this study as a relevant lens to nurses emotional labour. The attribution process has been shown to affect interactions in various serviceproviding scenarios including health care (Morrow et al 2011, Grayson et al 2014, Weiss et al 2014. Its connection to nurses' emotional labour, however, has only been recently implied (Crego et al 2013) and yet to be fully clear.…”
Section: What Are the Key Findings?mentioning
confidence: 99%
“…The same nurse might engage deep acting in certain encounters and surface acting in others. The attribution process has been shown to affect interactions in various serviceproviding scenarios including health care (Morrow et al 2011, Grayson et al 2014, Weiss et al 2014. Attribution theory (Weiner 1982) suggests that individuals act as naive psychologists in their desire to understand causes of events.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, individuals without personal experience may tend toward stigmatization because they are more likely to focus on internal causes of smoking. Indeed, Weiss et al 67 found that lung cancer patient advocates were more likely to know someone who was affected by cancer and more likely to believe that factors other than smoking (ie, genetics) were involved in the development of lung cancer. Thus, the model identified in the current study is consistent with well-established theories of attitude formation, but it applies this theory to a new area of public health.…”
Section: Discussionmentioning
confidence: 99%